Endovascular occlusion of pulmonary arteriovenous malformations with the ArtVentive Endoluminal Occlusion System™ - Corvino, Fabio (Diagn Interv Radiol, 2016)
Pulmonary arteriovenous malformations (PAVMs) are vascular anomalies of the lung and carry the risk of cerebral thromboembolism, brain abscess, or pulmonary hemorrhage. We describe a 64-year-old male with hereditary hemorrhagic telangiectasia (Osler-Weber-Rendu syndrome) who presented with a five-year history of progressive effort dyspnea and a PAVM in the right upper lobe successfully treated by transcatheter embolization of feeding arteries using a new occlusion device, the ArtVentive Endoluminal Occlusion System™.